In Vitro Activities of the Novel Ketolide Telithromycin (HMR 3647) against Erythromycin-Resistant Streptococcus Species - Jalava, Jari (American Society for Microbiology, 2001)
The in vitro susceptibilities of 184 erythromycin-resistant streptococci to a novel ketolide, telithromycin (HMR 3647), were tested. These clinical isolates included 111 Streptococcus pyogenes, 18 group C streptococcus, 18 group G streptococcus, and 37 Streptococcus pneumoniae strains. The MICs for all but eight S. pyogenes strains were ≤0.5 μg/ml, indicating that telithromycin is active in vitro against erythromycin-resistant Streptococcus strains. All strains for which MICs were ≥1 μg/ml had an erm(B) resistance gene and six strains for which MICs were ≥4 μg/ml had a constitutive erm(B) gene (MIC range, 4 to 64 μg/ml). Interestingly, for S. pneumoniae strains with a constitutive erm(B) gene, MICs were ≤0.25 μg/ml (MIC range, ≤0.008 to 0.25 μg/ml). Our in vitro data show that for S. pyogenes strains which constitutively express the erm(B) methylase gene, MICs are so high that the strains might be clinically resistant to telithromycin.